RESPONS GERAKAN KAPAL PERIKANAN HASIL OPTIMISASI TERHADAP GELOMBANG - Hutauruk, Ronald Mangasi; Rengi, Pareng (Jurnal Perikanan dan Kelautan, 2014)
The research was conducted on July to October with goal to obtain gilnetter performa in Maskom Village, District of Bengkalis through vessel response toward beam sea, following sea, and head sea. The vessel faces oscilatory motion in 6 degree of freedom. The vessel model was optimizing vessel in previous research. The principal dimension is LBP 14,0 m; B 2,8 m; H 2,4 m and T 1 m. It was modelled by using Maxsurf and continued using Seakeeper to ana-lyze Response Amplitude Operator (RAO) for instance pitching, rolling and heaving motion. Input data as vessel speed, feading angle and spectrum type was entered to depicts vessel re-sponse information. RAO for pithcing, rolling and heaving is between 1,1-8 and encountering frequency is in 0,22-0,6. It can be concluded that the vessel are decent to operate in the sea (seaworthies).